Geographies of plague pandemics the spatial-temporal behavior of plague to the modern day - Welford, Mark (Geographies of health series, 2018)
"Geographies of Plague Pandemics synthesizes our current understanding of the spatial and temporal dynamics of plague, Yersinia pestis. The environmental, political, economic, and social impacts of the plague from Ancient Greece to the modern day are examined. Chapters explore the identity of plague DNA, its human mortality, and the source of ancient and modern plagues. This book also discusses the role plague has played in shifting power from Mediterranean Europe to north-western Europe during the 500 years that plague has raged across the continent. The book demonstrates how recent colonial structures influenced the spread and mortality of plague while changing colonial histories. In addition, this book provides critical insight into how plague has shaped modern medicine, public health, and disease monitoring, and what role, if any, it might play as a terror weapon. The scope and breadth of Geographies of Plague Pandemics offers geographers, historians, biologists, and public health educators the opportunity to explore the deep connections among disease and human existence."--Provided by publisher